Relaxation-exchange magnetic resonance imaging (REXI): a non-invasive imaging method for evaluating trans-barrier water exchange in the choroid plexus - Xuetao Wu; Qingping He; Yu Yin; Shuyuan Tan; Baogui Zhang; Weiyun Li; Yi-Cheng Hsu; Rong Xue; Ruiliang Bai (Fluids and Barriers of the CNS, 2024)
Abstract Background The choroid plexus (CP) plays a crucial role in cerebrospinal fluid (CSF) production and brain homeostasis. However, non-invasive imaging techniques to assess its function remain limited. This study was conducted to develop a novel, contrast-agent-free MRI technique, termed relaxation-exchange magnetic resonance imaging (REXI), for evaluating CP-CSF water transport, a potential biomarker of CP function. Methods REXI utilizes the inherent and large difference in magnetic resonance transverse relaxation times (T 2s) between CP tissue (e.g., blood vessels and epithelial cells) and CSF. It uses a filter block to remove most CP tissue magnetization (shorter T 2), a mixing block for CP-CSF water exchange with mixing time t m, and a detection block with multi-echo acquisition to determine the CP/CSF component fraction after exchange. The REXI pulse sequence was implemented on a 9.4 T preclinical MRI scanner. For validation of REXI’s ability to measure exchange, we conducted preliminary tests on urea-water proton-exchange phantoms with various pH levels. We measured the steady-state water efflux rate from CP to CSF in rats and tested the sensitivity of REXI in detecting CP dysfunction induced by the carbonic anhydrase inhibitor acetazolamide. Results REXI pulse sequence successfully captured changes in the proton exchange rate (from short-T 2 component to long-T 2 component [i.e., k sl]) of urea-water phantoms at varying pH, demonstrating its sensitivity to exchange processes. In rat CP, REXI significantly suppressed the CP tissue signal, reducing the short-T 2 fraction (f short) from 0.44 to 0.23 (p < 0.0001), with significant recovery to 0.28 after a mixing time of 400 ms (p = 0.014). The changes in f short at various mixing times can be accurately described by a two-site exchange model, yielding a steady-state water efflux rate from CP to CSF (i.e., k bc) of 0.49 s−1. A scan-rescan experiment demonstrated that REXI had excellent reproducibility in measuring k bc (intraclass correlation coefficient = 0.90). Notably, acetazolamide-induced CSF reduction resulted in a 66% decrease in k bc within rat CP. Conclusions This proof-of-concept study demonstrates the feasibility of REXI for measuring trans-barrier water exchange in the CP, offering a promising biomarker for future assessments of CP function.